A Critical and Comparative Analysis of Teodoro Pérez’s Approaches to Caring and Demo-cratic Coexistence - Forero Baena, Carmen; Guerra Morales, Evelyn (Rastros Rostros, 2015)
This article expresses the Colombian society’s need to achieve coexistence in a caring and democraticway, and the desire to build spaces based on nurturing strategies that promote interaction. These ideasare complemented by the theories, laws and principles of Gestalt, the information processing ideas ofGagné, and the complex thinking of Morin. The aim of this article is to analyze the approaches andpositions of Teodoro Pérez in relation to maintaining spaces that are compatible with citizen respect,following a social and human development method. It is concluded that, despite the difficulty of thetask, and given its need, man must rediscover and understand himself, live in peace and share hisethos without selfishness
Keywords: coexistence; citizenship; democracy; solidarity